2014
DOI: 10.4161/15384101.2015.945375
|View full text |Cite
|
Sign up to set email alerts
|

Different fates of oocytes with DNA double-strand breaksin vitroandin vivo

Abstract: Abbreviations: DSBs, DNA double-strand breaks; GVBD, germinal vesicle breakdown; SAC, spindle assembly checkpoint; PB1, first polar body; IVM, in vitro maturation; MII, the second metaphase; MI, the first metaphase; DDR, DNA damage response; ICL, interstrand crosslinks; PBE, PB1 extrusion.In female mice, despite the presence of slight DNA double-strand breaks (DSBs), fully grown oocytes are able to undergo meiosis resumption as indicated by germinal vesicle breakdown (GVBD); however, severe DNA DSBs do reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…15 Severe DSBs also indirectly activate the SAC by disrupting kinetochore-microtubule attachment. 12 As shown above we found that a low NCS concentration (10 ng/ml) led to chromosome segregation problems in about 25% oocytes but a high NCS concentration (100 ng/ml) resulted in about 90% of the oocytes displaying problems with chromosome segregation (Fig. 1D).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…15 Severe DSBs also indirectly activate the SAC by disrupting kinetochore-microtubule attachment. 12 As shown above we found that a low NCS concentration (10 ng/ml) led to chromosome segregation problems in about 25% oocytes but a high NCS concentration (100 ng/ml) resulted in about 90% of the oocytes displaying problems with chromosome segregation (Fig. 1D).…”
Section: Resultsmentioning
confidence: 83%
“…12,13 Treating oocytes with a very high concentration of NCS (1mg/ ml) inhibits emission of the first polar body. 15 Severe DSBs also indirectly activate the SAC by disrupting kinetochore-microtubule attachment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse oocyte collection and culture were performed as previously described. 47 Oocytes were cultured in M2 medium supplemented with 2.5 mM milrinone to maintain them at the germinal vesicle (GV) stage. After specific treatments, oocytes were washed thoroughly and cultured in M2 medium to specific stages.…”
Section: Antibodiesmentioning
confidence: 99%